2017
DOI: 10.1186/s12936-017-1853-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activity of Indigofera spicata root extract against Plasmodium berghei infection in mice

Abstract: BackgroundIn addition to pharmacovigilance and pharmaco-economic concerns, resistance to anti-malarial medicines has been documented in all classes of anti-malarials and this is further worsened by resistance to common insecticides by malaria vector, which is a major threat to malaria control. As a means of facing the challenges of searching for new anti-malarial agents, the current study focused on evaluation of anti-malarial activity of root extract of Indigofera spicata.MethodsChloroquine-sensitive rodent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 28 publications
9
27
1
Order By: Relevance
“…The dose-dependent reduction in parasitemia levels produced by the methanol aerial extract of Alysicarpus glumaceus (average parasitemia 20.46 ± 1.31, 15.48 ± 1.37 and 12.26 ± 0.79 at 250, 500, and 1,000 mg/kg, respectively), is an indication of the extracts ability to inhibit the proliferation of Plasmodiumparasite in mice (Figure 3). The current finding agreed with other reports on medicinal plants used for malaria, such as Indigofera spicata, 8 Strycnos mitis 21 and Trema orientalis. 23 The oral median lethal dose was estimated to be greater than 5,000 mg/kg as there was no mortality recorded after the first and second phases of the acute toxicity study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The dose-dependent reduction in parasitemia levels produced by the methanol aerial extract of Alysicarpus glumaceus (average parasitemia 20.46 ± 1.31, 15.48 ± 1.37 and 12.26 ± 0.79 at 250, 500, and 1,000 mg/kg, respectively), is an indication of the extracts ability to inhibit the proliferation of Plasmodiumparasite in mice (Figure 3). The current finding agreed with other reports on medicinal plants used for malaria, such as Indigofera spicata, 8 Strycnos mitis 21 and Trema orientalis. 23 The oral median lethal dose was estimated to be greater than 5,000 mg/kg as there was no mortality recorded after the first and second phases of the acute toxicity study.…”
Section: Resultssupporting
confidence: 93%
“…7 These plants have served as sources for new drugs including some of the most successful antimalarial agents, such as quinine and artemisinin. 8 Alysicarpus glumaceus (Family-Fabaceae) is a shrubby annual plantwhich can grow up to 1 m high. The plant is found in the grassy savanna of Upper Volta, Northern Ghana and Northern Nigeria, and is also widely dispersed over the rest of tropical Africa.…”
Section: Introductionmentioning
confidence: 99%
“…However, non-significant difference was observed across all groups except Group 2 mice that were passaged but untreated. This result is consistent with (Birru et al, 2017), in which neither the extract doses nor the standard drug-treated group demonstrated statistically significant difference in body weight compared to the control group. The discrepancy was attributed to imbalance of the extract to potentiate protective effect and the cumulative pathophysiologic changes associated with the infection (Birru et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of red blood cells (RBCs) infected with malaria parasites were determined microscopically using the x100 objective with immersion oil in 10 different fields on each slide. The % Parasitemia and % Suppression were calculated using the formula (Birru et al, 2017):…”
Section: Measurement Of Parasitaemiamentioning
confidence: 99%
“…Plant extracts are considered active when reduction or percentage suppression in parasitemia is ≥ 30% or signi cant prolonging the survival time of treated mice compared to the vehicle control (38)(39)(40). Thus, the leaf latex of A. weloensis was found to be active against P. berghei infected mice.…”
Section: Discussionmentioning
confidence: 99%